Young children with severe congenital malformations (VACTERL) expressed mixed feelings about their condition and worries about needles and anaesthesia. (3rd August 2017) - Kassa, A‐M; Engvall, G; Engstrand Lilja, H
Abstract: Aim: Our knowledge of the perceptions that children with severe congenital malformations have of their health, treatment and how to improve hospital care is limited. This study focused on patients with vertebral defects, anal atresia, cardiac defects, tracheo‐oesophageal fistula, renal anomalies and limb abnormalities (VACTERL). Methods: We interviewed 10 children aged five to eight years with VACTERL association who were treated in a Swedish tertiary paediatric surgical centre, using a computer‐assisted technique called In My Shoes. The interviews were analysed by qualitative content analysis. Results: The children described their awareness of their health history and said they felt proud but different due to their physical dysfunction. They were happy to visit the hospital to meet familiar staff, but expressed negative feelings about missing normal life. They were afraid of needle‐related procedures and not wakening up after anaesthesia. Various ways of coping with difficult situations were expressed, and suggestions to improve hospital care were voiced. Conclusion: Careful follow‐up of these children by multidisciplinary teams is crucial to optimise their health and functional status. Fear of medical procedures may be reduced by carefully delivered information, listening to the children, providing continuity of care and creating individual care strategies.